Analisis Bibliometrik Peran Orang Tua terhadap Perkembangan Bahasa Anak Usia Dini - Erma Noviana Pratiwi; Purwandari, Eny (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Language development in early childhood is a crucial aspect influenced by the social environment, especially the role of parents as the child's closest figures. Parents play a strategic role in providing stimuli that accelerate children's language acquisition through communication, interaction, and modeling. Objectives: This article aims to examine the role of parents in the language development of early childhood through a theoretical review using a bibliometric approach. Methods: The method employed involves bibliometric analysis supported by Publish or Perish software for metadata collection and VOSviewer for literature mapping. Results: show that the keywords